1998
DOI: 10.21000/jasmr98010151
|View full text |Cite
|
Sign up to set email alerts
|

Successful Tree Planting Techniques for Drastically Disturbed Lands: A Case Study of the Propagationand Planting of Container-Grown Oak and Nut Trees in Missouri

Abstract: Successful tree seedling establishment on drastically disturbed lands is contingent on seven major variables: 1) selection of proper native species, 2) purchase of the best quality planting stock, 3) correct handling of planting stock, 4) correct planting techniques, 5) effective control of competing vegetation, 6) proper soil conditions and preparation, 7) weather. Exotic species should not be planted to avoid past mistakes such as kudzu, Japanese honeysuckle, sericea lespedeza and chestnut blight. A major co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Given that containerized seedlings maintain their entire root system when transplanted, transplant shock can be considerably reduced through use of containerized seedlings (Miller 1999;BCMOF 2001). Containerized seedlings also maintain higher water potential during the first year following out-planting compared to bareroot seedlings (Dixon et al 1983;Crunkilton et al 1992), which can further reduce shock to the seedling caused by site acclimatization.…”
Section: Stocktypementioning
confidence: 99%
“…Given that containerized seedlings maintain their entire root system when transplanted, transplant shock can be considerably reduced through use of containerized seedlings (Miller 1999;BCMOF 2001). Containerized seedlings also maintain higher water potential during the first year following out-planting compared to bareroot seedlings (Dixon et al 1983;Crunkilton et al 1992), which can further reduce shock to the seedling caused by site acclimatization.…”
Section: Stocktypementioning
confidence: 99%
“…The fact that microbial biomass was independent of other regressors in the model suggests microbial growth as a causative factor. In any case, microbes are a good indicator of soil health (Miller, 1998). Hutson (1980) found that low population densities of organisms on industrial reclamation sites led to significantly less degradation of oak leaves than on control sites.…”
Section: Microbial Biomassmentioning
confidence: 99%
“…This lack of soil organisms in mine spoils may result in poor soil development and thus lower tree survival and growth. In his discussion of techniques for reclaiming with native hardwoods, Miller (1998) stated that the development of a healthy and diverse soil microorganism population through replacement of topsoil is essential to the establishment of native trees. These microbes are the main mechanism for the release of plant available nutrients from organic matter (Brady and Well, 1996).…”
Section: Microbial Biomassmentioning
confidence: 99%
“…Production of seedlings by containers has many advantages over bare root stock such as quick production, uniform size, extending planting season, and performing well on adverse sites (Stein et al 1975;Tsakaldimi et al 2005). Moreover, container-grown seedlings generally have smaller shoot-toroot ratios and larger fine roots than bare root seedlings, that can adapt certain transplanting stresses such as drought (Miller 1999;Grossnickle and El-Kassaby 2016).…”
Section: Introductionmentioning
confidence: 99%